2010
DOI: 10.4103/1319-3767.61240
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of a giant hepatic hemangioma - sequential management with transcatheter arterial embolization and resection

Abstract: Hemangioma is the most common benign tumor of liver and is often asymptomatic. Spontaneous rupture is rare but has a catastrophic outcome if not promptly managed. Emergent hepatic resection has been the treatment of choice but has high operative mortality. Preoperative transcatheter arterial embolization (TAE) can significantly improve outcome in such patients. We report a case of spontaneous rupture of giant hepatic hemangioma that presented with abdominal pain and shock due to hemoperitoneum. Patient was suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…If not promptly and appropriately managed, all the above complications are associated with increased risk of mortality. [ 8 , 16 , 17 ] Reports on hepatic hemangioma with internal hemorrhage are rather rare; only a few are available worldwide. [ 18 20 ] In general, the ultrasound manifestations of hemangiomas are slightly enhanced echoes and have relatively clear demarcation unless complicated with hemorrhage, fibrosis, or calcification when hypoechoic changes are observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If not promptly and appropriately managed, all the above complications are associated with increased risk of mortality. [ 8 , 16 , 17 ] Reports on hepatic hemangioma with internal hemorrhage are rather rare; only a few are available worldwide. [ 18 20 ] In general, the ultrasound manifestations of hemangiomas are slightly enhanced echoes and have relatively clear demarcation unless complicated with hemorrhage, fibrosis, or calcification when hypoechoic changes are observed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] It is reported that the operative mortality rate of a ruptured hemangioma is about 36.5%. [ 8 ] For hemangiomas with spontaneously ruptured bleeding, interventional therapies are reported to achieve auxiliary or ideal therapeutic effects [ 10 , 23 ] ; therefore, we first adopted interventional approaches and found that the right phrenic artery was the blood supply vessel of the hemangioma. This condition, never seen in any previous literature, might share the same underlying pathogenesis of the hepatic carcinoma in which the huge and fast-growing tumor opens and dilates the collaterals between the phrenic and hepatic arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rare, it is associated with a high mortality rate. [ 7 ] Jain et al [ 8 ] reported a mortality rate ranging from 60% to 75% for spontaneous rupture with an operative mortality rate of 36.4%. Patients can die of massive hemorrhage in a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] However, the use of TAE as an alternative to surgery in the management of ruptured HHs remains controversial. [ 8 , 14 , 16 ] If the patient is stable, TAE prior to surgery may decrease intraoperative blood loss. [ 2 ] In hemodynamically unstable patients with spontaneous rupture of HH, operative treatment is the preferred choice.…”
Section: Discussionmentioning
confidence: 99%